Excess BMI in childhood: a modifiable risk factor for type 1 diabetes development? - Ferrara, CT; Geyer, SM; Liu, Y-F; Evans-Molina, C; Libman, IM; Besser, R; Becker, DJ; Rodriguez, H; Moran, A; Gitelman, SE; Redondo, MJ; Type 1 Diabetes TrialNet Study Group (American Diabetes Association, 2017)
OBJECTIVE We aimed to determine the effect of elevated BMI over time on the progression to type 1 diabetes in youth.